2005
DOI: 10.1007/s00449-005-0024-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic kinetic resolution: alternative approach in optimizing S-ibuprofen production

Abstract: A lipase catalysed enantioselective hydrolysis process under in situ racemization of the remaining (R)-ibuprofen ester substrate with sodium hydroxide as the catalyst was developed for the production of S-ibuprofen from (R,S)-ibuprofen ester in isooctane. Detailed investigations on parameters study indicated that 0.5 M NaOH, addition of 20% (v/v) co-solvent (dimethyl sulphoxide), operating temperature of 45 degrees C, and 40 mmol/L substrate gave 86% conversion and 99.4% optical purity of S-ibuprofen in dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 23 publications
0
28
0
1
Order By: Relevance
“…Thus, further studies were performed on immobilized tannase on amberlite. Amberlite is considered to be better immobilization matrix for various other enzymes such as urease (Anita et al, 1997), lipase (Fazlena et al, 2006), and R-galactosidase (Onal and Telefoncu 2005), and fructosyltransferase (Platková et al, 2006).…”
Section: Immobilization Of Tannasementioning
confidence: 99%
“…Thus, further studies were performed on immobilized tannase on amberlite. Amberlite is considered to be better immobilization matrix for various other enzymes such as urease (Anita et al, 1997), lipase (Fazlena et al, 2006), and R-galactosidase (Onal and Telefoncu 2005), and fructosyltransferase (Platková et al, 2006).…”
Section: Immobilization Of Tannasementioning
confidence: 99%
“…The undesired enantiomer (R)-ibuprofen was racemized in basic ethylene glycolwater (It has been reported that (R)-ibuprofen ethoxyethyl ester can be racemized in basic DMSO-water. 19 ) and then re-resolved. The (S)-ester was separated and hydrolyzed to produce (S)-ibuprofen.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, Candida rugosa lipase, 15,16 Rhizomucor miehei lipase, 17 and Aspergillus niger lipase 8 have been used for the chiral resolution of (R,S)-ibuprofen through mainly direct enantioselective esterification in organic media; Lipase from C. rugosa (Type VII), 18,19 Pseudomonas cepacia lipase, 20 and Pseudomonas fluorescens lipase 21 have been used to catalyze enantioselective hydrolysis of its chemically synthesized racemic ester.…”
Section: Introductionmentioning
confidence: 99%
“…The value of enantioselectivity ( E ) was calculated from the enantiomeric excess of the substrate ( ee ) and the conversion degree ( c ) according to the equations 1 and 2 described by Chen et al [23]. …”
Section: Methodsmentioning
confidence: 99%